Atrial Fibrosis by Late Gadolinium Enhancement Magnetic Resonance Imaging and Catheter Ablation of Atrial Fibrillation: 5‐Year Follow‐Up Data. Issue 23 (4th December 2018) - Chelu, Mihail G.; King, Jordan B.; Kholmovski, Eugene G.; Ma, Junjie; Gal, Pim; Marashly, Qussay; AlJuaid, Mossab A.; Kaur, Gagandeep; Silver, Michelle A.; Johnson, Kara A.; Suksaranjit, Promporn; Wilson, Brent D.; et al.
Abstract : Background: Late gadolinium enhancement magnetic resonance imaging is an effective tool for assessment of atrial fibrosis. The degree of left atrial fibrosis is a good predictor of atrial fibrillation (AF) ablation success at 1 year, but the association between left atrial fibrosis and long‐term ablation success has not been studied. Methods and Results: Late gadolinium enhancement magnetic resonance images of sufficient quality to quantify atrial fibrosis were obtained before the first AF ablation in 308 consecutive patients. Left atrial fibrosis was classified in 4 Utah stages (I, 0–10%; II, 10–20%; III, 20–30%; and IV, >30%). Patients were followed up for up to 5 years until the time of first arrhythmia recurrence or second ablation. A total of 308 patients were included; the mean age was 64.5±12.1 years, and 63.4% were men. During follow‐up, 157 patients experienced an arrhythmia recurrence and 106 patients underwent a repeated ablation. A graded effect was observed in which patients with more advanced atrial fibrosis were more likely to experience recurrent AF (hazard ratio for stage IV versus stage I, 2.73; 95% confidence interval, 1.57–4.75) and undergo a repeated ablation (proportional odds ratio for stage IV versus stage I, 5.19; 95% confidence interval, 2.12–12.69). Conclusions: The degree of left atrial fibrosis predicts the success of AF ablation at up to 5 years follow‐up. In patients with advanced atrial fibrosis, AF ablation is associated with a high procedural failure rate.